(untitled) (Research, Society and Development, 2022)
Animal fat plays a fundamental role in guaranteeing the physical, sensorial and technological properties of emulsified meat products. However, the high consumption of saturated fats from emulsified meat products increases the risk of metabolic diseases. Therefore, there is a need to study viable alternatives for the replacement of saturated fat. The use of gel emulsions, gelled structures based on vegetable oils that can be combined with proteins and hydrocolloids, stands out. Therefore, the present study aimed to carry out bibliographic research on the production and use of emulsion gels and their behavior when applied to meat products. The results showed that the use of emulsion gels is able to maintain or improve the technological characteristics of emulsified meat products. Therefore, it is inferred that it is of paramount importance that research on the application of vegetable oils in emulsion gels be carried out and applied to meat products.